2018
DOI: 10.3762/bjoc.14.10
|View full text |Cite
|
Sign up to set email alerts
|

Gram-scale preparation of negative-type liquid crystals with a CF2CF2-carbocycle unit via an improved short-step synthetic protocol

Abstract: Herein, we demonstrate an improved short-step protocol for the synthesis of multicyclic molecules having a CF2CF2-containing cyclohexadiene or cyclohexane framework in a mesogenic structure. These molecules are promising candidates for vertical alignment (VA)-mode liquid crystal (LC) display devices owing to their large negative dielectric constant. The tetrafluorinated multicyclic molecules were successfully obtained in only five or six reaction steps without the need for special handling techniques, as is ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Among the obtained compounds, 2‐acetyl‐2‐chlorocyclohexan‐1‐one 1 o provided the spiro product 6 oa in good yield (56%) as single diastereoisomer, and 2‐chloro‐2,2‐difluoroacetophenone 1 r quantitatively furnished the fluorinated hemiketal 6 ra . Only Konno and co‐workers obtained products with a similar substituents distribution but exploiting a much longer synthetic pathway [72,75] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the obtained compounds, 2‐acetyl‐2‐chlorocyclohexan‐1‐one 1 o provided the spiro product 6 oa in good yield (56%) as single diastereoisomer, and 2‐chloro‐2,2‐difluoroacetophenone 1 r quantitatively furnished the fluorinated hemiketal 6 ra . Only Konno and co‐workers obtained products with a similar substituents distribution but exploiting a much longer synthetic pathway [72,75] …”
Section: Resultsmentioning
confidence: 99%
“…These highly substituted cyclopentyl hemiketals ( 6 ) are useful synthetic intermediates, [71] in particular for the preparation of materials [72] and medicinally relevant molecules [73] . Our approach represents a particularly straightforward synthesis of these scaffolds, which were obtained for the first time in high yield by radical addition of ketones to olefins [74] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, our group has pursued the development of fluorine-containing organic materials and has developed negative-type LC molecules with the CF 2 CF 2 -containing carbocycles A and the mesogenic structure B [17][18][19]. Moreover, the scope of π-conjugated photoluminescence (PL) molecules was extended to include a pentafluorinated aromatic scaffold, as exemplified by fluorinated tolanes C and bistolanes D (Figure 1a) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the development of a convenient access to CF 2 CF 2 -containing pyranoses [ 12 ], our group also showed that tricyclic mesogens with a CF 2 CF 2 -containing carbocycle exhibited large negative dielectric anisotropies ( Fig. 1 ), which would be promising for candidates for vertically aligned (VA)-type display materials [ 13 17 ]. Owing to such valuable applications, the development of a much more efficient synthetic protocol for CF 2 CF 2 -containing organic molecules has a high priority in various research areas.…”
Section: Introductionmentioning
confidence: 99%